Perceptual Coding of High-Quality Digital Audio - Brandenburg, Karlheinz; Faller, Christof; Herre, Jürgen; Johnston, James D.; Kleijn, W. Bastiaan (Proceedings of the IEEE, 2013)
This paper introduces high-quality audio coding using psychoacoustic models. This technology is now abundant, with gadgets named after a standard (mp3 players) and the ability to play high-quality audio from literally billions of devices. The usual paradigm for these systems is based on filterbanks, followed by quantization and coding, controlled by a model of human hearing. The paper describes the basic technology, theoretical framework to apply to check for optimality, and the most prominent standards built on the basic ideas and newer work. © 1963-2012 IEEE.
herre_books_journals
Keywords: Audio coding